Analisis Hukum Islam terhadap Putusan Hakim tentang Hak Asuh Anak yang Belum Mumayyiz Akibat Perceraian - Naura Syahira Firmayuni; Encep Abdul Rojak; Yandi Maryandi (UNISBA Press, 2024)
Abstract. The custody of a child who has not yet reached the age of discernment (mumayyiz) after a divorce, according to Article 105 of the Compilation of Islamic Law, belongs to the mother. However, in decision number 155/Pdt.G/2024/PA.Tmk, the judge rejected the petition for child custody submitted by the plaintiff, who is the biological mother of the children. The purpose of this research is to understand the judge's considerations in deciding case number 155/Pdt.G/2024/PA.Tmk regarding the custody of a child who has not yet reached the age of discernment and to review the Islamic legal perspective on this decision. This research uses a qualitative method with a multidisciplinary approach, namely a normative Shari'a approach and a normative juridical approach. Data collection techniques include interviews and documentation. Data analysis techniques involve data reduction and drawing conclusions. The results of this research conclude that since the child is currently living with the father, the child remains under the father's care. The panel of judges assessed that since the child is not prevented from meeting the mother and continues to live with the father without any significant harm to either party in the caregiving process, the judge rejected the mother's custody petition. The panel of judges decided that the child can continue to be cared for jointly by both parents for the best interest of the child. This judicial decision aligns with one of the legal principles in Islamic jurisprudence, “Government decisions are based on considerations of public welfare.” This is because in the ruling, the judge not only focused on the prevailing legal norms but also considered the welfare of the child. Abstrak. Hak Asuh anak yang belum mumayyiz setelah terjadinya perceraian dalam Kompilasi Hukum Islam pasal 105 adalah hak ibu. Namun pada putusan nomor 155/Pdt.G/2024/PA.Tmk hakim menolak petitum hak asuh anak yang di ajukan oleh penggugat selaku ibu kandung dari anak-anaknya tersebut. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pertimbangan hakim dalam memutus perkara nomor 155/Pdt.G/2024/PA.Tmk mengenai hak asuh anak yang belum mumayyiz serta bagaimana tinjauan hukum Islam terhadap putusan perkara nomor 155/Pdt.G/2024/PA.Tmk mengenai hak asuh anak yang belum mumayyiz. Penelitian ini menggunakan metode kualitatif dengan pendekatan multidisipliner yakni pendekatan normatif syar'i serta pendekatan yudiris-normatif. Teknik pengumpulan data menggunakan wawancara dan dokumentasi. Teknik analisis data meliputi reduksi data dan penarikan kesimpulan. Hasil penelitian ini menyimpulkan bahwa karena saat ini anak tinggal bersama ayahnya, maka anak masih dalam asuhan sang ayah. Majelis Hakim menilai bahwa karena anak tidak dihalangi bertemu dengan ibunya dan tetap tinggal bersama ayahnya tanpa adanya kerugian yang nyata bagi salah satu pihak dalam proses pengasuhan maka hakim menolak petitum hak asuh ibu. Majelis Hakim memutuskan bahwa anak dapat tetap diasuh bersama oleh kedua orang tuanya demi kepentingan terbaik anak. Putusan hakim ini sejalan dengan salah satu kaidah fikih “Ketetapan atau kebijakan pemerintah dibangun dengan pertimbangan kemaslahatan”. Karena dalam putusannya hakim tidak hanya berfokus pada norma hukum yang berlaku namun juga melihat pada sisi kemaslahatan anak.